REVEALING STUDENTS' NARRATIVE WRITINGS: ITS PROBLEMS AND ALTERNATIVES BY MAKING USE OF VISUAL IMAGES - Intan Sinta Dewi Rahayu; Wawan Gunawan; Eri Kurniawan (Edusentris, 2020)
Writing a narrative text, although it is just so stories, requires a creative imagination and sufficient knowledge of its genre. This paper aims to find out the students’ difficulty in writing narrative text and offers the pedagogical implication to alternate it. Document analysis was employed to compare narrative texts produced by an expert and three students within SFL framework focusing on experiential meaning. The findings show that the experiential meaning was not well-construed in the students’ texts. The students have not richly developed the plot into a more imaginative story due to the simplicity of the series of events, particularly in the complication stage, the lack of circumstance to build the setting of the story, and the improper number of process types, except material process, signified with the frequent repeated lexical choice. To address the students’ difficulty of building the field of the story, this paper provides a practical pedagogical implication of SFL, experiential meaning in particular, for teaching narrative writing by making use of visual images following Genre-Based Approach and multimodal approach. This paper is expected to contribute to the SFL in teaching practice and inspire EFL teachers to design a creative narrative teaching by using the visual images.